2006
DOI: 10.1086/503055
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Competing Disease Risks: Implications for Host Populations in Variable Environments

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 69 publications
(57 reference statements)
1
34
0
Order By: Relevance
“…There are examples from the animal disease literature illustrating synergy, antagonistic, and neutral population-level interactions among competing pathogens (Rohani et al 2003, Jolles et al 2006, 2008. Results from the present study indicate an apparently neutral impact of E. maimaiga on the density dependence of LdNPV in North American gypsy moth populations.…”
Section: Discussionmentioning
confidence: 47%
“…There are examples from the animal disease literature illustrating synergy, antagonistic, and neutral population-level interactions among competing pathogens (Rohani et al 2003, Jolles et al 2006, 2008. Results from the present study indicate an apparently neutral impact of E. maimaiga on the density dependence of LdNPV in North American gypsy moth populations.…”
Section: Discussionmentioning
confidence: 47%
“…Pathogens can reduce host density and, in some cases, drive their host populations to extinction (McCallum and Dobson 1995;Tompkins and Begon 1999;De Castro and Bolker 2005;Jolles et al 2006). Paradoxically, many populations suffering from a variety of infectious diseases are relatively stable (Albon et al 2002;Caley et al 2002;Krkosek et al 2011;Tobler et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Disease-induced mortality causes host population declines only if it is additive to other sources of host mortality (i.e. competition or predation; Anderson and May 1979;Burnham and Anderson 1984;Tompkins et al 2002;Jolles et al 2006). In contrast, when mortality is compensatory, increases in disease-induced deaths are balanced by a reduction in natural mortality from other causes (Tompkins and Begon 1999;Lebreton 2005;Jolles et al 2006), and populations will remain stable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study specifically testing this assumption found it to be flawed (Freeman and Morgan, 1992). Other examples of key 24 ecological assumptions that have been found to be erroneous when empirically tested include: (1) that disease acts independently of other mortality-causing factors in mammal epidemiological models (tested by Jolles et al, 2006); (2) that a "typical" age structure can be applied to fish populations to accurately assess densitydependent productivity effects (tested by Zabel and Levin, 2002) and (3) that island communities are more 28 susceptible to biological invasion than continental landmasses (tested by Sol, 2000). Importantly, the use, whether implicit or explicit, of such erroneous assumptions reduces the validity of the research results predicated upon them (Thompson, 2002).…”
Section: Introductionmentioning
confidence: 99%